Heparin-Induced Thrombocytopenia in Infants after Heart Surgery - Abdillah, Juma N.; Hu, Qinghua; Chen, Xuliang; Chen, Xing; Zhou, Wu; Luo, Wanjun; Huang, Lingjin (The Thoracic and Cardiovascular Surgeon, 2019)
Background Heparin-induced thrombocytopenia (HIT) in infants is a rare disorder, and the diagnosis and management of HIT still remains challenging. Argatroban is a synthetic direct thrombin inhibitor (DTI) that is widely used for treating HIT. However, little is known about the efficacy of the activated clotting time (ACT) test in monitoring DTI treatment as an alternative to the routinely used activated partial thromboplastin time (aPTT).Methods Between July 2013 and January 2015, four infants were diagnosed with HIT after surgical correction of congenital anomalies. In all cases, heparin was used during cardiopulmonary bypass (CPB). Diagnosis of HIT was based on the “4 Ts” pretest clinical scoring system, and platelet factor 4 (PF4) antibody was detected using enzyme-linked immunosorbent assay. Argatroban was used in treating HIT. When argatroban was infused, anticoagulation tests (aPTT, prothrombin time [PT], thrombin time [TT], and fibrinogen) were performed every 4 to 12 hours. ACT was used in addition to monitor the anticoagulation effect of argatroban. The target ACT was 1.5 to 3.0 times the baseline. ACT was measured every 2 to 4 hours and remeasured 1 hour after each dosage adjustment.Results Thrombocytopenia (defined as a 50% decrease in platelet count) occurred during the 3rd to 6th day postoperatively. After the diagnosis of HIT, argatroban was started immediately, and platelet counts stabilized and gradually increased. Anticoagulation effect of argatroban was successful monitored by ACT and aPTT. Poor correlation between the ACT test and aPTT test (R = 0.270, p = 0.092) was noted in one patient. ACT values increased rapidly after 3 to 7 days on argatroban treatment. In most cases, low dosage of argatroban was given ranging from 0.04 to 5.00 μg/kg/min.Conclusion Argatroban may be an effective medicine in treating HIT in infants, in a reduced dosage. The great fluctuation in argatroban dosage during the course of HIT treatment necessitates close monitoring. ACT test may be reliable and convenient for monitoring HIT treatment and may contribute to positive clinical outcomes in infants. The efficacy of argatroban and the use of ACT monitoring in the management of HIT infants needs further study.
Keywords: Infant; heart surgery; heparin; thrombocytopenia; argatroban; activated coagulation time